AB0359 TNF ALFA THERAPY AND RADIOSYNOVIORTHESIS IN PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Szentesi, M.; Nagy, Z.; Karoly Mangel, Z.; Csőre, G.; Géher, P.
Abstract : Background: The treatment of patients with rheumatoid arthritis (RA) has been spectaculary changed since the 1950's. Introduction of the steroid compounds and their local application, the chemical and radionuclide synovectomy, surgical synovectomy, use of non steroid drugs, the basic treatment and the spread of biological therapy are the most important steps. Introduction of the biological therapy has changed the quality of life for these patients. Objectives: During biological therapy sometimes 1 or 2 joints could be affected by inflammation. In this cases always the question is how to solve the problem. Change of the biological or basic therapy, use surgical synovectomy or radiosynovectomy (RSO)? Methods: In our reumatological department 2100 patients with RA were treated with biological therapy between 2002 and 2018. In 100 patients we applied RSO because of the inflammation of the knee joint during biological therapy. We made a long term follow-up in 82 patient. All participants provided written informed consent. 82 participants inflammatory knee joint disease was diagnosed on the basis of the American College of Rheumatology. 70 of 82 patients with rheumatoid arthritis were seropositive, 12 seronegative. Steinbrocker functional stadium II was observed in 72, stadium III in 10. Mean age of 18 male and 76 female patients was 51.4 years (range 24-79) years. In 42 patients the right knee, in 40 the left knee was treated by radiosynovectomy. Mean duration of disease was 8.3 years (range 0.5-25), of synovitis (6.3month (range 3-8) Mean number of punctions of the treated joint prior to radiosynovectomy was 4, 2 per patient and of steroid administrations prior to radiosynovectomy 3, 0. In 15 patients a systemic steroid therapy has been performed. Results: During the study period, inflammation decreased. In the first 3 years excellent and good results were recorded in 81, 2%. 3 years after radiosynoviorthesis 82.2% of patients did not need another punction. Before the knee inflammation patients were in complete remission which status has been achieved after RSO as well. DAS: 2, 4+-0, 4. Conclusion: 1. RSO is an effective method to treat the inflammation of the knees. 2. The RSO performed during biological tehrapy is as effective as in the case of patients without biological therapy. 3. In case of a successful RSO there is no need for biological or basic therapy neither for surgical synovectomy. 4. However an intraarticular injection has a low risk for infection it is recommended to avoid the biological therapy during the RSO. References: [1]WHO Scientific Group, 2003 [2]Szekanecz Z.: Célzott terápia a reumatológiában. Klinikum és Tudomány, MOTESZ Magazin; 2010;XVIII(2):31–44. [3]McInnes IB, Schett G. Cytokines in the pathogenesis of rheumatoid arthritis. Nat Rev Immunol. 2007 Jun;7(6):429-42 [4]Klippel JH. Primer on the Rheumatic Disease. 12th ed. 2001. [5]Lipsky PE. Harrison's Principles of Internal Medicine. 16th ed. 2005 [6]EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update [7]Fellinger K. and Schmid J.: Die lokale Behandlung der rheumatischen Erkrankungen. Z. Inn. Med. 33. 351. 1952. [8]Watanabe M., Takeda S., Ikeuchi H.: Atlas of arthroscopy 2nd ed. Tokyo: Igaku Shoin 1969. [9]Stucki G., Bozzone P., Treuer E., Wassmer P. and Felder M.: Efficacy and safety of radiation synovectomy with Yttrium-90: A retrospective long term analysis of 164 applications in 82 patients. British J. of Rheumatology 32. 5. 383-386. 1993. [10]Combe B., Krause E. and Sany J.: Treatment of chronic knee synovitis with arthroscopic synovectomy after failure of intra-articular injection of radionuclide. Arthritis Rheum. 32. 1. 10-14. 1989. Disclosure of Interests: None declared